Reinterpreting menopause : cultural and philosophical issues / edited by Paul A. Komesaroff, Philipa Rothfield, and Jeanne Daly. - Komesaroff, Paul A.; Rothfield, Philipa; Daly, Jeanne (Routledge, 1997)
Reinterpreting Menopause brings together a number of reflections from a broad range of areas including feminism, cultural studies, clinical medicine, sociology, philosophy, and political science and includes the voices and experiences of menopausal women themselves. In an innovative series of essays, current thinking about medicine, society, and the body is critically examined. Particular attention is given to the medical representations of menopause, biology and aging, the history of medical approaches to women, and the tensions between bio-medical models and other explanations of menopause. The issues of hormonal therapies are explored in the context of the connections between women, medicine, representations, and cultural politics.
Keywords: Menopause.; Middle-aged women -- Health and hygiene.; Middle-aged women -- Psychology.; Middle aged women -- Psychology.